Obesity paradox in cognitive function: a longitudinal study of BMI and cognitive impairment in older adult Chinese population - Chen, Jing; Zhang, Jun; Wang, Hao; Zhu, Hongliang; Fu, Jialin; Li, Chuanwei; Zhang, Qingrong; Xia, Xingzhi; Ma, He; Liu, Junjun; Du, Xiangdong (Frontiers in Aging Neuroscience, 2025)
ObjectiveThis study endeavored to investigate the correlation between body mass index (BMI) and cognitive impairment in the demographic of Chinese individuals who are 60 years of age and above.MethodsWe selected data from China Health and Retirement Longitudinal Study (CHARLS) 2015–2018 and 2,942 subjects aged ≥60 years were included. The Mini-Mental State Examination (MMSE) was used to assess cognitive impairment. BMI was examined in two forms: as a continuous variable and was stratified into tertiles. Analysis was conducted using both univariate and multivariate logistic regression. Non-linear relationships were analyzed using curve fitting and segmented logistic regression.ResultsDuring the study, 600 out of 2,942 subjects (20.4%) experienced cognitive impairment. In fully adjusted models, each unit increase in BMI was related to a 4% decrease in the odds of cognitive impairment (OR: 0.96, 95% CI: 0.93–0.99, p = 0.008). There was a noticeable protective effect from the highest BMI tertile in comparison to the lowest tertile (OR: 0.64, 95% CI: 0.50–0.83, p < 0.001). Non-linear analysis revealed an inflection point at BMI of 26.60 kg/m2, with a significant inverse relationship below this point (OR: 0.96, 95% CI: 0.93–0.99, p = 0.008) and no substantial association above it.ConclusionThis study provides evidence supporting the “obesity paradox” in the cognitive function of older adult Chinese population. Higher BMI is linked to lower cognitive impairment risk, especially among overweight persons. These findings indicate a complex and non-linear link between BMI and cognitive health among older adult adults, emphasizing the importance of tailored strategies for weight management in this population.